ISOLASI DAN IDENTIFIKASI FUNGI ENDOFIT BATANG SESURU (Euphorbia antiquorum L.) SEBAGAI PENGHASIL ANTIBAKTERI DENGAN METODE KLT-BIOAUTOGRAFI - Asnita Asnita; Herwin Herwin; Rachmat Kosman; Ayyub Harly Nurung (As-Syifaa Jurnal Farmasi, 2020)
The  research  aimed  to  obtain antibacterial  activity  of  isolate  fermentate  of  endophytic  fungi  of  antique spurge stem (Euphorbia antiquorum L.) on Staphylococcus aureus and Escherichia coli by TLC-Bioautography. The methods used in this research were isolation, purification and isolate screening. The  screening results of endophytic  fungi isolate  of  antique  spurge  stem  showed  the  largest  inhibitory  zone  in preventing  both  bacteria  growth  using  code  IFBS-03  and  IFBS-06.  The chromatogram profile  of antibacterial activity isolate fermentate  of the codes IFBS-03  and  IFBS-06  showed  active  spots  using  TLC-Bioautographic method showed that code IFBS-03 isolate obtained Rf 0.87 and 0.27 values, indicating active spots on  Staphylococcus aureus  and  Escherichia coli. The result of code IFBS-06 isolate obtained Rf 0.83 value active spots against Staphylococcus aureus and  values  Rf  0.83  and  0.27  value on  Escherichia  coli.  Based on isolation and identification some chemical components obtained that dietyl ether ekstract of thin layer cromatography obtained chemicals components flavanoid at Rf 0.83 and 0.27 value with reagent Antimo (III) chloride.